Pengaruh Model Pembelajaran Terhadap Kemampuan Memecahkan Masalah Lingkungan Hidup Pada Siswa yang Mempunyai Hasil Belajar IPA Tinggi di Sekolah Dasar - Irianto, Dede Margo (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2014)
The aim of the research is to identify the influence of learning model and IPA Science learning on the ability to solve problem in learning environmental education at the elementary school. This research was conducted in SD Laboratorium UPI Kampus Cibiru Bandung. Experimental method with factorial plan 2 x 2 is the method that was employed in this study. The sampling objects were 40-fourth grade students. Twenty of them achieved high learning outcomes in environmental study meanwhile the remains were having low learning outcomes. Two ways varian analysis (ANAVA) was used in hypothesis test and then continued by Turkey test. The research conclusion were: Students with high learning outcomes in science had better ability to solve environmental problems using constructivist learning model than interactive learning model;